Body by science : a research based program for strength training, body building, and complete fitness in 12 minutes a week - McGuff, Doug (McGraw-Hill, 2009)
Explains the role of exercise in health, and suggests a workout routine that emphasizes high-intensity, low-frequency weight training, and de-emphasizes more traditional aerobic-centered exercise.